Ten-Gram-Scale Mechanochemical Synthesis of Ternary Lanthanum Coordination Polymers for Antibacterial and Antitumor Activities - Zhang, Liying; Shi, Haoran; Tan, Xiao; Jiang, Zhenqi; Wang, Ping; Qin, Jieling (Frontiers in Chemistry, 2022)
As rare earth coordination polymers (CPs) have appreciable antimicrobial properties, ternary lanthanum CPs have been widely synthesized and investigated in recent years. Here, we report convenient, solvent-free reactions between lanthanum salt and two ligands at mild temperatures that form ternary lanthanum nanoscale CPs with ten-gram-scale. The structural features and morphologies were characterized using scanning electron microscope (SEM), fourier transform infrared spectrometer (FT-IR), ultraviolet-visible (UV-Vis), X-ray diffractometer (XRD), X-ray Photoelectron Spectroscopy (XPS), Brunauer-Emmett-Teller (BET), elemental analysis, inductively coupled plasma mass spectrometry (ICP-MS), electrospray ionization mass spectrometry (ESI-MS), nuclear magnetic resonance (NMR), dynamic light scattering (DLS) and analyzer and thermogravimetric and differential thermal analyzer (TG-DTA). Furthermore, the in vitro antibacterial activities of these ternary hybrids were studied using the zone of inhibition (ZOI) method, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and Transmission electron microscope (TEM), and were found to have excellent antibacterial properties. The in vitro antitumor activities were performed in determining the absorbance values by CCK8 (Cell Counting Kit-8) assay. This facile synthetic method would potentially enable the mass production of ternary lanthanum CPs at room temperature, which can be promising candidates as antibacterial compounds and antitumor agents.